Methyl cellulose-based solid polymer electrolytes with dispersed zinc oxide nanoparticles: A promising candidate for battery applications. (February 2023) - Jayalakshmi, K.; Ismayil,; Hegde, Shreedatta; Ravindrachary, V.; Sanjeev, Ganesh; Mazumdar, Nirmal; Sindhoora, K.M.; Masti, Saraswati P.; Murari, M.S.
Abstract: Novel solid polymer electrolytes based on methyl cellulose (MC) and magnesium chloride (MgCl₂⋅ 6H₂O) have been prepared by a solution casting technique. The best conducting polymer electrolyte system has been doped with different amounts of zinc oxide (ZnO) nanoparticles to assess their effect on its properties. Structural studies by FTIR and XRD analysis have revealed complete complexation between the polymer host and the dopant. A polymer electrolyte system with 25 wt% of the salt exhibited the highest room temperature ion conductivity of 1.18 × 10⁻⁴ S cm⁻ 1 with excellent thermal and dielectric properties. The dispersal of ZnO nanoparticles therein served to enhance the conductivity. SEM micrographs reveal complete dispersion of the nanofiller on the electrolyte surface. A primary battery has been fabricated, and its open-circuit potential and discharge characteristics have been studied. Overall, the prepared electrolytes have excellent properties and may thus be promising candidates for energy storage devices. Highlights: MC:MgCl₂:ZnO polymer electrolytes were prepared by solution casting technique. XRD and FTIR analysis confirmed the complexation of the salt with polymer matrix. Incorporation of nanofiller improves the mechanical stability & ionic conductivity. Battery prepared using this electrolyte exhibited good open circuit voltage.